Pesniške reprezentacije negotovosti - Tokarz, Bożena (Primerjalna književnost, 2016)
This article presents forms and strategies of representing uncertainty in contemporary Polish poetry, which over the past century has used various strategies, ranging from the alternative structuring of signs, the portrayal of mechanisms of the current psychosphere, and a system of activities to expressing uncertainty in antithetic, interrogative, and situational structures.
Keywords: poljska poezija; semiotics; semiotika; pesniški jezik; znak; reprezentacija; negotovost